Upaya Promosi Pariwisata Daerah melalui Pelatihan Penyelenggaraan Pentas Seni Sekolah di Kecamatan Pangalengan, Kabupaten Bandung - Nindi Aristi (Jurnal Pengabdian Pada Masyarakat, 2020)
REGIONAL TOURISM PROMOTION EFFORTS THROUGH TRAINING OF SCHOOL ARTS PERFORMANCES IN PANGALENGAN DISTRICT, BANDUNG REGENCY. Regional tourism promotion which has so far focused on using conventional publication media such as tourism exhibitions and advertisements in the mass media is considered to be less effective because the targets are generale and require quite a large amount of funds. School art performances can be a tourism promotion media especially for young teenagers and are useful in promoting new and unique tourist attractions. Through community service activities aimed at providing basic knowledge about performing arts up to the end of the activities of madrasa students willing and able to become actors and activists of tourism promotion. The existence of this activity is a tangible manifestation of the active participation of educational institutions in the promotion of tourism in the District of Pangalengan and supports the efforts of the Regional Government to increase Local Revenue (PAD) through tourism.